Three-Dimensional Imaging in Stem Cell-Based Researches - Nowzari, Fariborz; Wang, Huimei; Khoradmehr, Arezoo; Baghban, Mandana; Baghban, Neda; Arandian, Alireza; Muhaddesi, Mahdi; Nabipour, Iraj; Zibaii, Mohammad I.; Najarasl, Mostafa; Taheri, Payam; Latifi, Hamid; et al. (Frontiers in Veterinary Science, 2021)
Stem cells have an important role in regenerative therapies, developmental biology studies and drug screening. Basic and translational research in stem cell technology needs more detailed imaging techniques. The possibility of cell-based therapeutic strategies has been validated in the stem cell field over recent years, a more detailed characterization of the properties of stem cells is needed for connectomics of large assemblies and structural analyses of these cells. The aim of stem cell imaging is the characterization of differentiation state, cellular function, purity and cell location. Recent progress in stem cell imaging field has included ultrasound-based technique to study living stem cells and florescence microscopy-based technique to investigate stem cell three-dimensional (3D) structures. Here, we summarized the fundamental characteristics of stem cells via 3D imaging methods and also discussed the emerging literatures on 3D imaging in stem cell research and the applications of both classical 2D imaging techniques and 3D methods on stem cells biology.